The end of a natural monopoly : deregulation and competition in the electric power industry - Grossman, Peter Z., 1948-; Cole, Daniel H., 1958- (Amsterdam ; Boston : JAI, 2003)
After decades of the presumption that the electric power industry was a natural monopoly, recent times have seen a trend of deregulation followed by panicked re-regulation. This title addresses the fundamental issues underlying the debate over electric power regulation and deregulation from a legal and economic perspective.
Includes bibliographical references.
oif 16/09/15
Loan
Keywords: Electric utilities -- Deregulation; Electric utilities -- Deregulation -- United States